(untitled) (Research, Society and Development, 2020)
SARS-CoV-2 belongs to the family of coronaviruses and is an infectious disease that threatens public health worldwide. The definitive diagnosis of the new coronavirus is made by molecular tests used in breathing tests, such as, for example, or rubbing the throat. However, most of the time, infectious diseases are diagnosed employing symptoms, laboratory, and image exams, like x-ray, computed tomography, and nuclear magnetic resonance imaging. The present study aimed to analyze the main imaging tests found in the respiratory syndrome caused by the new coronavirus. This research deals with a narrative review of the literature published so far, having a descriptive and qualitative nature. A search took place in the databases of virtual health libraries. It was refined by Latin American and Caribbean Literature in Health Sciences (LILACS), Electronic Scientific Library (SCIELO), BIREME (Regional Library of Medicine), and MEDLINE. Among the authors published, the occurrence of ground-glass opacities, isolation, or multifocal, consolidations such as cardiomegaly, decreased air space, aerobocograms, and pleural effusion were observed. Also, some findings had atypical characteristics. We conclude that in several formed patterns found to characterize a lung disease, with main optional bilateral, peripheral, and essential features, with rounded morphologies, presence of lymph node enlargement, pleural effusion, excavation, and nodules in the most severe cases. In this way, it is suggested that the imaging exams be complementary to the laboratory diagnosis.